1999
DOI: 10.1007/s004249900112
|View full text |Cite
|
Sign up to set email alerts
|

Calcium release induced by high K+ and caffeine in cultured skeletal muscle cells of embryonic chicken

Abstract: To further understand the function of excitation-contraction coupling in skeletal muscle cells developing in vitro, Ca2+ transients elicited by high-K+ depolarization in the presence and absence of extracellular Ca2+ were compared with Ca2+ release induced by caffeine in cultured skeletal muscle cells isolated from 9-day-old chicken embryos (E9). Almost all myoblasts and myotubes cultured for 1 (E9I1) to 8 (E9I8) days responded to 80 mM [K+]O with an elevation of [Ca2+]i. Although all myotubes cultured for mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
3
1
0
Order By: Relevance
“…This is in line with previous reports on skeletal muscle EC coupling using either K + -induced depolarization or electric stimulation (27)(28)(29). The initial, relatively fast decay phase likely corresponds to the binding of cytosolic Ca 2+ to fast Ca 2+ buffers (troponin) (30).…”
Section: +supporting
confidence: 78%
See 2 more Smart Citations
“…This is in line with previous reports on skeletal muscle EC coupling using either K + -induced depolarization or electric stimulation (27)(28)(29). The initial, relatively fast decay phase likely corresponds to the binding of cytosolic Ca 2+ to fast Ca 2+ buffers (troponin) (30).…”
Section: +supporting
confidence: 78%
“…In contrast, the slow decay phase displayed a higher variability for both cell types and slower rates in iPS-myocytes. Interestingly, it has been shown that the slow component of the intracellular Ca +2 decay becomes faster with vertebrate development (27)(28)(29) (31). Taken together, our data suggest that the slow Ca 2+ buffering processes that follow muscle contraction may still remain immature under these culture conditions in both cell types and to a higher extent in iPS-myocytes.…”
Section: +supporting
confidence: 66%
See 1 more Smart Citation
“…4A) on control, T95-myotubes, or on T51-myotubes by changing to 140 mM KCl. It resulted, as expected (27)(28)(29), in an increase in intracellular calcium concentration followed by a return to the basal level in control myotubes as well as in T51-myotubes. Nevertheless, in T95-myotubes, this effect was almost abolished, and depolarization induced only a minor calcium release (Fig.…”
Section: Trisk 95 or Trisk 51 Overexpression Does Not Modify Expressisupporting
confidence: 76%